Analysis of Key Drivers Influencing Airline Ticket Purchases at a Conventional Travel Agency in Bandung - Widiyanti, Rikantini; Gusniarti , Raflina Syifa (Journal of Tourism Sustainability, 2025)
Shifting consumer travel behavior and the dominance of online platforms have challenged the relevance of traditional travel agencies such as XYZ Travel Agency, a conventional service provider based in Bandung. This study aims to identify the key drivers of airline ticket purchase decisions using a quantitative approach and Confirmatory Factor Analysis (CFA). A structured questionnaire consisting of 23 indicators was distributed to 106 respondents. The results reveal four key influencing factors: (1) brand popularity and price appeal, including brand recognition and competitive pricing; (2) credibility, reflecting trust, reputation, and information accuracy; (3) competitive pricing, defined by price–value alignment and service transparency; and (4) service convenience and efficiency, encompassing responsiveness, route variety, and ease of transactions. These findings indicate that customer decisions are influenced by more than price alone—brand trust, service quality, and perceived value are also critical. To remain competitive, traditional travel agencies must enhance brand presence, provide reliable, accessible services, and align their offerings with evolving customer expectations.